This Isn't the Way I Thought It Would Be: Coping with a Child's Chronic Illness - Ashley Eckes; Heidi Liss Radunovich; Susan Brumbaugh (EDIS)
FCS-2295, a 7-page fact sheet by Ashley Eckes, Heidi Liss Radunovich, and Susan Brumbaugh, provides parents guidance through the process of finding out that their child has a chronic illness, how the diagnosis may affect the child and the family unit, and sources of help and support. Includes references. Published by the UF Department of Family Youth and Community Sciences, January 2009.